19. KNOWLEDGE AND ATTITUDE ABOUT HANDLING INJURIES CAUSED BY SHARP OBJECTS OF MEDICAL STAFF AT NATIONAL HOSPITAL OF ACUPUNCTURE IN 2022 (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the knowledge and attitudes about handling injuries and current situation of injury caused by sharp objects of the medical staff at the National Hospital of Acupuncture in 2022. Subject and method: A Cross-sectional descriptive study using self-completed interview questions to collect research data. The study was conducted from August to December 2022. Results: Of the total 130 subjects participating in the study, 76.2% of subjects had correct knowledge and 93.8% of subjects who participated in the study had a positive attitude about handling injuries caused by sharp objects. In the past year, 46.2% of study participants were injured by sharp objects, of which 60% of research participants correctly practiced post-exposure injury management. Conclusion: Most medical staff at National Hospital of Acupuncture have good knowledge and positive attitudes about treating injuries caused by sharp objects. However, when injuries occur, many healthcare workers still do not practice proper injury management to protect their health from the risks of disease.
Keywords: Knowledge, attitude, injury treatment, sharp objects, National Hospital of Acupuncture.